Determinantes sociais de saúde e as implicações do distanciamento social na saúde psíquica e ocupacional de pessoas idosas - Tuchtenhagen, Pétrin Hoppe (2022)
The Social Determinants of Health are considered permanent indicators of life, being social, economic, cultural, ethnic-racial, psychological and behavioral factors that influence people's health. At the beginning of 2020, the Coronavirus Pandemic emerged, an infectious disease, which put the world population at risk. On the occasion, the World Health Organization declared the viral infection by COVID-19 a Public Health Emergency, asking countries to carry out projects to control the spread of the virus, provoking government officials to adopt social distancing measures. As the elderly are the first population related to the health care of the new disease, it was verified through the social determinants of health, the psychological and occupational impacts of distancing in the lives of elderly people during the Covid-19 pandemic. A cross-sectional and analytical study was developed, addressing social distancing and the social determinants of health as exposure to psychological and occupational implications. The field research was carried out with elderly people in the Municipality of Agudo, from October 2021 to January 2022. The most identified factor in the research was the prevalence (87.5%) of non-communicable chronic diseases in the population. Another finding was that the majority of the population routinely participated in weekly groups, and these directly influenced their socialization, contributing to an improvement in their health conditions and, consequently, their quality of life. There was a constancy of responses that referred to social distancing as a factor that interfered in the psychic conditions of the elderly people interviewed. It was observed that there was a limitation of the process of occupational participation, identifying the concept of occupational deprivation with regard to the restriction of significant occupations in everyday life.